1999
DOI: 10.1210/jc.84.1.291
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Regulation of Prostaglandin Dehydrogenase Activity and Expression in Human Term Placenta and Chorio-Decidua in Relation to Labor

Abstract: NAD+-dependent 15-hydroxyprostaglandin dehydrogenase (PGDH) is the key catabolic enzyme controlling levels of biologically active PGs. PGDH is localized to syncytiotrophoblast in placenta, and to trophoblast cells in chorion. To examine the regulation of PGDH by steroids and to determine any changes with labor, we obtained placenta and chorion from term elective cesarean section or spontaneous delivery and isolated trophoblast cells using a Percoll density gradient. Cells were treated with varying concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 0 publications
7
50
0
4
Order By: Relevance
“…PGDH mRNA expression is increased by progesterone (23). The inhibitory effect of cortisol on PGDH activity seems to be mediated by the mineralocorticoid receptor, as has been demonstrated recently (15,24).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…PGDH mRNA expression is increased by progesterone (23). The inhibitory effect of cortisol on PGDH activity seems to be mediated by the mineralocorticoid receptor, as has been demonstrated recently (15,24).…”
Section: Discussionmentioning
confidence: 60%
“…This enables prostaglandins to reach the myometrium, increasing its contractility (18,23). With respect to the chorion, previous investigators have shown a reduction of PGDH gene expression and activity more often in patients with spontaneous labour than in patients who underwent caesarean section (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids inhibit PGHS-2 transcription and reduce PGHS-2 mRNA stability (DeWitt and Meade, 1993;Evett et al, 1993), representing one pathway of anti-inflammatory action. However, several studies have shown that PG production in cultured amnion and chorion is stimulated by cortisol and the synthetic glucocorticoid dexamethasone (Novy and Walsh, 1983;Mitchell et al, 1988;Potestio et al, 1988;Zakar and Olson, 1989;Gibb and Lavoie, 1990;Smieja et al, 1993;Economopoulos et al, 1996;Patel et al, 1999;Blumenstein et al, 2000;Whittle et al, 2000b). The amnion consists of a single layer of epithelial cells and a subepithelial mesenchymal layer.…”
Section: Regulation Of Prostaglandin Synthesismentioning
confidence: 99%
“…Studies directed towards understanding the mechanism by which steroid hormones might regulate PGDH (Patel et al, 1999) (Fig. 3) have also revealed a mechanism for local progesterone withdrawal within the human fetal membranes.…”
Section: Prostaglandin Metabolismmentioning
confidence: 99%
See 1 more Smart Citation